(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
The article scientifically substantiates the role of the Movarounnahr school of Hadith studies within the context of the spiritual and educational reforms implemented in New Uzbekistan. It highlights that the science of Hadith is not merely a religious source, but an intellectual and ethical phenomenon that ensures intercultural dialogue and social stability.